Developing Skills and Disposition for Lifelong Learning: Acculturative Issues Surrounding Supervising International Doctoral Students in New Zealand Universities - Li, Mingsheng (Journal of International Students, 2016)
This study examines the acculturative challenges facing non-English speaking background (NESB) international doctoral students in the process of discipline enculturation. Twenty NESB doctoral students at three New Zealand universities from eleven countries participated in the semistructured interviews. The study has found that their transformative learning was the result of happiness, joy, success, and transformative disposition for lifelong learning as well as various challenges, plights and hardships. The dynamic interplay of the dichotomy fosters their intercultural competence, critical thinking, research skills, independence, and academic scholarships, and prepares them for new challenges and multiple academic demands. It is argued that developing capacities and disposition for lifelong learning should be facilitated through disciplinary enculturation, skills development, familiarity with academic conventions, and effective mentoring and healthy supervisor-supervisee relationships.